Challenger banks in Iceland : disrupting the traditional deposit market? - Daniel Piotr Roczkowski 2001-; Helena Pétursdóttir 1976- (2024)
This research examines the changes in the Icelandic banking sector following the entrance of the challenger banks, Auður and Indó, and substantial technological advancements. The researchers examined how these new entrants have affected the existing oligopoly structure and the broader competitive landscape within the industry, mainly through market disruption driven by strategies that prioritize transparency and ethical banking practices. The research methodology includes a comparative analysis of interest rates from late 2018 to February 2024, evaluating how Iceland’s three major banks, Landsbankinn, Íslandsbanki, and Arion Banki responded to the competitive pressure applied by the challengers. The findings suggest that the entrance of Auður has led to a noticeable decrease in the gap between the Central Bank´s key interest rate and those rates offered to consumers, benefiting customers without additional risk. Furthermore, Indó's entry has sparked an important awakening among consumers. This new competition has driven an increasing demand for transparency and fairness within the banking sector. As a result, traditional banks are therefore forced to reevaluate and adapt their strategies to a changed financial landscape.